Legal Protection for Contract Workers in the Hospitality Sector Based on Human Rights: An Analysis of Law Number 6 of 2023 on Manpower: Perlindungan Hukum Tenaga Kontrak di Perhotelan Berbasis Hak Asasi Manusia (Analisis Undang-Undang Nomor 6 Tahun 2023 Tentang Ketenagakerjaan) - Tri Andani; Mohammad Tohari; Surya Kusuma Wardana (CV Edujavare Publishing, 2026)
Persistent job insecurity marks the experience of many contract workers in the hospitality industry, as their agreements tend to be short and are repeatedly renewed without a clear trajectory toward permanent status. This paper traces how legal protection for hotel contract workers actually operates under Law Number 6 of 2023 on Manpower, using human rights as its analytical lens, while mapping the obstacles and possible remedies involved. The study was conducted through a sociological-juridical method, combining normative review with field data gathered from interviews with contract employees at Hotel Grasia Semarang, supplemented by literature review. The data collected reveal that although the prevailing labor regulation is arguably adequate on paper, on-the-ground conditions fall well short of that ideal: contracts keep being extended without any clarity on eventual permanent hiring, workers lack a full grasp of the rights attached to their status, and their bargaining power sits well below that of hotel management. Viewed through a human rights lens, such conditions erode the right to decent work and the right to legal certainty guaranteed by the constitution. In closing, the paper proposes tighter labor inspection, ongoing dissemination of contract workers' rights, and reform of contract governance to better balance employer and worker interests.